Como se de ventre livre nascesse: experiências de cativeiro, parentesco, emancipação e liberdade nos derradeiros anos da escravidão – Rio Pardo/RS, c.1860 - c.1888 - Perussatto, Melina Kleinert (Universidade do Vale do Rio dos Sinos, 2010)
This study has a proposal to investigate captivity experiences, blood relations, emancipation and freedom lived by slave workers (and people who were in almost the same condition) in the last decades of slavery (1860 ? 1888). Therefore, we mainly use the crossing of numbers and names of various sources. As a local to observation the Rio Pardo County, situated in the central region of São Pedro do Rio Grande do Sul province and linked by river to Porto Alegre, the province?s capital which both had commercial relations established. Its economy was based also in cattle and agriculture both to respond internal demands. As in the majority of the counties in São Pedro do Rio Grande do Sul province Rio Pardo had a predominance of minor slaves owners whose work force was disseminated by practically every productive activities and areas. The equilibrium between genders and the presence of young workers at the slavery sites in almost three decades visited by this work among many post-mortem inventories made us to question the importance of endogenous slave reproduction at the captivity just before the abolition and also the family configurations made by those slaves. Under this aspect the projects and the strategies of freedom produced by afro descendents families included their properties conquered, the constitution of spiritual ties and the appropriation of legal rights (the law of September 28 of 1871 above all, known as the Free Venter Law), all of these were among the legal right resources available and, for that instance, were commonly used. Slaves that didn?t have that kind of family ties made their presences among those who were seeking for freedom - that exceeds the simple symbolization of changing the captivity situation - were operating by working adjustments in this reorganization of the labor relations context. The year of 1884, in this way, has its importance ?cause it marks the province?s emancipation strategy of liberating under some work conditions as many slaves as possible - all of this made to the slaves owners not to loose their moral power. Adding to that, the presence of free children from slaves mothers inventoried among the ex-slaves owners properties as also the requests of guardianship linked to the use of these children work force yet made us to question the attributes presents in the kind of freedom these subjects had in their near captivity experiences. The today situation of slaves? descendents is equally pointed in this study by a presentation of experiences of an afro community located at Rio Pardo County that lives in lands donated to their ancestors in the slavery times and that resists to expropriation nowadays. In the end we must point that the senses of justice and rights manifested by these historical subjects relating the captivity situation, the manumission, family and freedom will be mainly explicated in this work.
Keywords: Cativeiro; Família; Alforria; Liberdade; Rio Pardo; Captivity; Family; Manumission; Freedom; Rio Pardo County; ACCNPQ::Ciências Humanas::História